Gain smoothening filter in two-segment fiber-optical parametric amplifier - Adikan, Faisal Rafiq Mahamd; Yeo, K.S.; Mokhtar, M.; Hitam, S.; Mahdi, M.A. (Elsevier, 2013)
This paper demonstrates a method to remove the gain ripple profile specifically for a two-segment fiber optical parametric amplifier arising from the dispersion differences between the fiber gain medium and the standard single mode fiber attached to the optical components.This is achieved by using a simple design that incorporates again smoothening filter at the mid-stage of the amplifier.This simple yet practical method is useful when isolators are adopted for stimulated Brillouin scattering suppression but it comes with the expense of parametric gain.